Sediment-Nitrogen (N) connectivity: suspended sediments in streams as N exporters and reactors for denitrification and assimilatory N uptake during storms - Joshi, Bisesh; Bacmeister, Eva; Peck, Erin; Peipoch, Marc; Kan, Jinjun; Inamdar, Shreeram (Frontiers in Water, 2023)
Nitrogen (N) pollution in riverine ecosystems has substantial environmental, economic, and policy consequences. Various riverine N removal processes include permanent dissimilatory sinks such as denitrification (Uden) and temporary assimilatory sink such as microbial N uptake (Uassim). Both processes have been extensively evaluated in benthic sediments but only sparsely in the water column, particularly for storm flows producing high suspended sediment (SS) concentrations. Stormflows also increase the sediment bound N (Sed-N) export, and in turn, the overall N exports from watersheds. The balance between N removal by Uden and Uassim vs. Sed-N export has not been studied and is a key knowledge gap. We assessed the magnitude of Uden and Uassim against stormflow Sed-N exports for multiple storm events of varying magnitude and across two drainage areas (750 ha and 15,330 ha) in a mixed landuse mid-Atlantic US watershed. We asked: How do the Uden and Uassim sinks compare with Sed-N exports and how do these N fluxes vary across the drainage areas for sampled storms on the rising and falling limbs of the discharge hydrograph? Mean Uden and Uassim as % of the Sed-N exports ranged between 0.1–40% and 0.6–22%, respectively. Storm event Uassim fluxes were generally slightly lower than the corresponding Uden fluxes. Similarly, comparable but slightly higher Uden fluxes were observed for the second order vs. the fourth order stream, while Uassim fluxes were slightly higher in the fourth-order stream. Both of these N sinks were higher on the falling vs. rising limbs of the hydrograph. This suggests that while the N sinks are not trivial, sediment bound N exports during large stormflows will likely overshadow any gains in N removal by SS associated denitrification. Understanding these N source-sink dynamics for storm events is critical for accurate watershed nutrient modeling and for better pollution mitigation strategies for downstream aquatic ecosystems. These results are especially important within the context of climate change as extreme hydrological events including storms are becoming more and more frequent.